2017
DOI: 10.1002/2017ja024504
|View full text |Cite
|
Sign up to set email alerts
|

Whistler Wave Propagation Through the Ionosphere of Venus

Abstract: We investigate the attenuation of whistler waves generated by hypotetical Venusian lightning occurring at the altitude of the cloud layer under different ionospheric conditions. We use the Stanford full‐wave method for stratified media of Lehtinen and Inan (2008) to model wave propagation through the ionosphere of Venus. This method calculates the electromagnetic field created by an arbitrary source in a plane‐stratified medium (i.e., uniform in the horizontal direction). We see that the existence of holes in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Hence, we cannot measure distances between the lightning source locations and whistler exit points. It is important to note that the inclination of the lightning channel influences the propagation of the emitted waves (Pérez‐Invernón, Lehtinen, et al,; Pérez‐Invernón, Luque, et al, ). Although this inclination may influence the relative intensities of MWR and Waves received signals, a small number of only eleven concurrent events in this study does not allow us to investigate this influence.…”
Section: Jovian Whistler and Sferic Analysismentioning
confidence: 99%
“…Hence, we cannot measure distances between the lightning source locations and whistler exit points. It is important to note that the inclination of the lightning channel influences the propagation of the emitted waves (Pérez‐Invernón, Lehtinen, et al,; Pérez‐Invernón, Luque, et al, ). Although this inclination may influence the relative intensities of MWR and Waves received signals, a small number of only eleven concurrent events in this study does not allow us to investigate this influence.…”
Section: Jovian Whistler and Sferic Analysismentioning
confidence: 99%
“…Although they are often discussed as traveling parallel to the magnetic field, oblique whistler waves were also detected (Cattell et al., 2008) and prompted further studies (Artemyev et al., 2016; Ma et al., 2017; Yoon et al., 2014). Furthermore, whilst they were originally discovered in Earth's magnetosphere, spacecraft observations showed that whistler waves also occur in solar wind (Narita et al., 2016) and the atmospheres of Venus (Pérez‐Invernón et al., 2017) and Jupiter (Imai et al., 2018). This study will focus on whistling behavior in Earth's magnetosphere at parallel, oblique, and perpendicular propagation, and how it is affected by the occurrence of avoided crossings compared to parallel propagation (De Jonghe & Keppens, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ion heating by whistler waves has importance in many research field starting from laboratory plasmas to space and astrophysical plasmas, in the diagnostics of the material structures, medicine, security and industrial engineering. 12,13 Also in plasma-based fusion science, it is necessary to heat the plasma ions for efficient fusion reaction to occur. [1][2][3][4] Whistler wave is basically a low frequency right circularly polarized (RCP) electromagnetic mode having a frequency which is lower than the electron cyclotron frequency associated with the ambient constant magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic features and propagation characteristics of whistler waves have been studied extensively in the past. [5][6][7]9,[12][13][14] This mode has a unique attribute of non-existence of cut-off which enables it to propagate through over-dense plasma system 5,[15][16][17][18] . The relativistic theory developed by Akheizer and Polovin in 1956 7 clearly shows how even in over-dense plasma system whistler waves can readily propagate without any cut-off density.…”
Section: Introductionmentioning
confidence: 99%